The triangular relationship between Danish, Nordic, and European law - Magnus Esmark (European Law Open)
In this Article, I show how Danish reception of EC/EU law has been shaped by Nordic law and the connections between Danish and other Nordic jurists in a triangular system of social arenas. The purpose is to show in a concrete case that understanding the history of EU law in Member States requires us to engage increasingly with its connections to transnational legal orders and social structures that are older and different to the EU. In this, I aim to contribute to a history and sociology of EU law that puts its contingency at the forefront and removes EU from the main stage. The Article is based on the archives of the Nordic Jurist Meetings, a triennial conference of Nordic jurists dating back 150 years. I contextualise the debates with contemporary developments in the reception of EC/EU law within Denmark. I argue that Nordic law has played a special role in the history of EC/EU law in Denmark, as a source of reciprocal legitimation between the legal elites of the five Nordic countries. Whereas the Danish legal elite first believed in synergy between Nordic and EC law, the increased use of EU law to challenge this very elite during the 1990s onwards made them see Nordic law as in a principled, values-based opposition to European law. I argue that engagement in Nordic law has shaped Danish jurists’ perception of EU law, just as it has been mobilised in a defence of the Danish legal order against EU law.